Hands-On Exploration of Cubes’ Floating and Sinking Benefits Children’s Subsequent Buoyancy Predictions - van Schaik, Johanna E.; Slim, Tessa; Franse, Rooske K.; Raijmakers, Maartje E. J. (Frontiers in Psychology, 2020)
Children accrue experiences with buoyancy on a daily basis, yet research paints a mixed picture of children’s buoyancy knowledge. Whereas children’s predictions and explanations of the floating and sinking of common objects are often based on a single feature (e.g. mass or facts), children’s predictions of novel cubes reveal solution strategies based on mass and volume integrations. Correspondingly, category learning theory suggests that categories (e.g. floaters vs. sinkers) are easier to identify when items mainly vary from one another in the relevant, defining features. For example, a set of cubes only varies in mass and volume, and hence density, thereby being able to highlight the deterministic role of density when placed in water. Here, we asked how item variation during hands-on exploration affects children’s subsequent predictions and explanations of buoyancy. Kindergarteners and first, second, and third grade children individually explored either a set of ten systematically varied cubes (i.e. systematic condition; n = 95) or a set of ten common objects (i.e. non-systematic condition; n = 96) in a water basin. Next, children predicted the buoyancy of five new cubes and five new common objects one at a time. Subsequently, children explained their predictions one subset at a time. Children in the systematic condition were more accurate in their predictions of the test cubes than children in the non-systematic condition. Latent Class Regression Analyses identified three cube prediction solution strategies. Children in the systematic condition were more likely to use a strategy in which buoyancy decisions were made based on an accurate integration of mass and volume, while children in the non-systematic condition were more likely to use a strategy in which mass was given more predictive load than volume. A third strategy was characterized by guessing. Latent Class Analyses of children’s explanations revealed different explanation strategies, each appealing to several features, but, as hypothesized, no clear condition differences were found. The findings indicate that even five minutes of exploration with systematically-varied cubes can already help children use an advanced buoyancy prediction strategy. This provides evidence in favor of using category learning theory to inform early science education design.